ANALYSIS OF THE ATTITUDES OF THE POPULATION ON THE NEED FOR ANIMAL INSURANCE - Piljan, Tatjana; Brzaković, Tomislav; Šmigić-Miladinović, Jasmima (Economics of Agriculture, 2019)
Agriculture in the Republic of Serbia is a sector of economy that is vital for the overall social and economic development of the country. The position of the agrarian sector in Serbia is specific, since, besides the economic importance, there is also a special social and ecological significance, and agriculture contributes to the national wealth with significant participation in the creation of GDP. Animal insurance involves a large number of risks and is classified as risk insurance. It belongs to the group of short-term insurance or insurance for up to one year, and even shorter. The subject of insurance is the animal itself, and not just certain parts of the animals body or manufactures that can be obtained from it. The subject of this research is to examine the attitudes of the respondents regarding the necessity of animal insurance and the problems that arise in this case.